Transient Heat Transfer Analysis on Composite Solids for Hypersonic Flow Applications - Peetala, Ravi (Trends in Sciences, 2022)
Surface heating rates have the importance in high speed flow due to viscous or aerodynamic heating which leads to enormous rise in surface temperature. Prediction of exact heat transfer rates is essential for design of protection systems for aerodynamic bodies aimed. For the thermal protection system, the aerodynamic Surfaces are generally configured with multiple solids. Hence present study is planned to develop the conjugate heat transfer (CHT) solver for composite solids. A CHT solver is in hypersonic flow environment. Finite volume framework and explicit time stepping have been implemented for both the compressible Navier-Stokes solver and conduction solver. Loose coupling has been established between the above mentioned fluid and solid domain solvers. The following observations were made in the CHT simulations. In the case of hypersonic flows over finite thickness flat plate, considerable difference in surface heat transfer rate has been noticed along the stream wise direction at the solid-fluid interface and also the Effect of wall material on heat diffusion for hypersonic application has been analyzed using loosely coupled CHT solver. The CHT solver has also been implemented for hypersonic flow over composite cylinder. Necessity of insulating material in the region of stagnation point has been realized as the outcome of these studies. HIGHLIGHTS Accurate prediction of Convective heating rates is essential for the design of thermal protection system for hypersonic vehicles In The thermal protection system, the aerodynamic surfaces are generally configured with multiple solids. Hence the present study is planned to develop the conjugate heat transfer (CHT) solver for composite solids The CHT solver has been implemented for hypersonic flow over composite flat plate and cylinder. It has been observed flows over finite thickness flat plate, a considerable difference in surface heat transfer rate has been noticed along the stream wise direction at the solid-fluid interface and the necessity of insulating material in the region of stagnation point has been realized as the outcome of these studies GRAPHICAL ABSTRACT